FINANCE APPLICATION - Prashant S. Bhandare1,Soham D. Shinde2,Swapnil L. Gawali2,Om S. Vastre2 ,Atharv M. Lambore2 (International Journal of Innovations in Engineering Research and Technology, 2022)
Every shopkeeper has one problem to attract the customer and sell the product. With thisconcept we are going to introduce the application that is “Finance Application”. It helps theshopkeeper to sell her product with EMI. And, for customer it is very useful to see how muchEMI is pending. There is so many facilities for customer like remainder of EMI.The project entitled "Finance Application" is system which contains an android application foruser, desktop software for admin. This project is mainly designed for android mobile sellers.This project helps sellers to sell mobiles on EMI. Seller can create his own EMI system. Sothat they can customize & manage their Interest Rate, Down Payments, No of EMIs, Paymentof EMIs, etc. Seller can sell devices to known people although they have less civil score andthe main benefit is that seller gets all margins, processing fees and interests which werecharged by finance companies previously. This system increases sells, profit margin and alsohelps to build better customer relation.Android App in this software pack, is designed to show EMI details such as next EMI date,remaining EMIs, invoices of EMIs N to provide Payment Gateway to make payment ofupcoming EMI. The main purpose of application is to send warning and lock device if usersdoesn’t make payment of EMI.Desktop Software is mainly designed for admin (Seller). From here admin can manage allcustomer relationships; admin can add connections, analysis EMI payments, etc. And there isalso backend designed to store n update data and to communicate with user and admin.